Skilling up Vietnam: Preparing the Workforce for a Modern Market Economy - Bodewig, Christian (World Bank, 2015)
Education has played an important role in making Vietnam a development success story over the last twenty years. In the 1990s and early 2000s Vietnam experienced rapid economic growth and poverty reduction in the wake of a rapid shift of employment from low-productivity agriculture to higher-productivity nonfarm jobs.